2011
DOI: 10.4236/ojog.2011.13027
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and perception of assisted reproductive technology practice amongst women with infertility in Northern Nigeria

Abstract: Background: Involuntary infertility is a tragedy in most African setting. This is due to premium placed on fertility as a result of roles children fulfill in the family and the society. Aetiologic factors of infertility in sub-Saharan Africa are mostly infection related and they are mainly associated with poor treatment outcome to conventional non assisted conception technique. Objective: To evaluate the level of awareness and perception of assisted conception treatment among women attending fertility clinic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 14 publications
(18 reference statements)
2
20
1
Order By: Relevance
“…Most of the respondents who were sexually active 6 months prior to the survey had only one heterosexual partner, though all who had 2-3 heterosexual partners were males and those who had ≥4 were females. A survey of adults aged 20-59 indicated that women have an average of 4 sex partners during their lifetime and men have an average of 7 [10], a record supported by the other study [11]. Reporting multiple sexual partnership is thus more common among males than among females [12].…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Most of the respondents who were sexually active 6 months prior to the survey had only one heterosexual partner, though all who had 2-3 heterosexual partners were males and those who had ≥4 were females. A survey of adults aged 20-59 indicated that women have an average of 4 sex partners during their lifetime and men have an average of 7 [10], a record supported by the other study [11]. Reporting multiple sexual partnership is thus more common among males than among females [12].…”
Section: Discussionsupporting
confidence: 48%
“…Almost equal proportions of the medical students thought that both husband and wife (11,8.7%) on one hand and neither (10,7.9%) on the other hand, were commonly blamed for infertility.…”
Section: Who Is Commonly Blamed For Infertility In the Society?mentioning
confidence: 99%
“…Another major challenge is the wrong perceptions and beliefs among the non-enlightened majority in developing countries particularly in West Africa about infertility and some of the available treatments (Adesiyun et al, 2011;Okwelogu et al, 2012;Omokanye et al, 2017;Okafor et al, 2017;Akande et al, 2019). Some believed that infertility is caused by evil spirits, predestined by God, punishment from God and supernatural challenge.…”
Section: Perception and Beliefmentioning
confidence: 99%
“…Infertile couples and the people around them were more aware of the ARTs (Afshani, Abdoli, Hashempour, Baghbeheshti & Zolfaghari, 2016). Another study in Nigeria revealed that 76.5% of infertile women heard about assistive reproductive techniques (Adesuyin, Ameh, Avidime & Muazu, 2011).…”
Section: Heard About Surrogacymentioning
confidence: 99%